2020
DOI: 10.1111/1467-9817.12330
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of single word spelling in English speaking children: a cross sectional study

Abstract: Background: The study aimed to explore to what extent variables associated with lexical and sublexical spelling processes predicted single word spelling ability and whether patterns of lexical and sublexical processes were different across ages. Methods: Beginning (mean age 7 years, N = 144) and advanced (mean age 9 years, N = 114) English-speaking spellers completed tasks associated with sublexical processing (phonological ability and phonological short-term memory), lexical processing (visual short-term memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 57 publications
1
17
1
Order By: Relevance
“…No reliable pattern emerged from the investigation of typical readers. While some studies reported no or weak VAS-PA relationships (Bosse & Valdois, 2009;Marinelli, Zoccolotti, & Romani, 2020;Niolaki et al, 2021), others found the two skills to be more highly correlated (from .41 to .45) (Valdois, Lassus-Sangosse, et al, 2019;Valdois, Roulin, & Bosse, 2019; Van den Boer & de Jong, 2018;Van den Boer, van Bergen, & de Jong, 2014). Variations in the tasks that were used to measure PA or in the language and age of participants (and whether the effect of age and IQ was controlled for, or not) may well account for these inconsistencies.…”
Section: Vas Relationship With Phonological Skillsmentioning
confidence: 99%
“…No reliable pattern emerged from the investigation of typical readers. While some studies reported no or weak VAS-PA relationships (Bosse & Valdois, 2009;Marinelli, Zoccolotti, & Romani, 2020;Niolaki et al, 2021), others found the two skills to be more highly correlated (from .41 to .45) (Valdois, Lassus-Sangosse, et al, 2019;Valdois, Roulin, & Bosse, 2019; Van den Boer & de Jong, 2018;Van den Boer, van Bergen, & de Jong, 2014). Variations in the tasks that were used to measure PA or in the language and age of participants (and whether the effect of age and IQ was controlled for, or not) may well account for these inconsistencies.…”
Section: Vas Relationship With Phonological Skillsmentioning
confidence: 99%
“…In the dimension of mappings, the optimum range is reached when the linguistic domains of lexical representations are well interconnected or when orthographic, phonological, and semantic elements “have been amalgamated” (Niolaki et al, 2020, p.591). The links between the individual domains of a representation are established and sufficiently strong so that the whole information about the lexical entry can be easily retrieved at an encounter with any domain.…”
Section: Introductionmentioning
confidence: 99%
“…This seems to be the case. Indeed, there is growing evidence that visual attention is a concurrent and longitudinal predictor of word reading fluency (Bosse & Valdois, 2009;Chan & Yeung, 2020;Valdois et al, 2019;van den Boer & de Jong, 2018) and word spelling acquisition (Niolaki et al, 2020;Valdois et al, submitted;van den Boer et al, 2015) and that individuals with reduced visual attention capacity are slow readers and poor spellers (Bosse et al, 2007;Chen et al, 2019;Valdois et al, 2011;Valdois et al, 2021;Zoubrinetzky et al, 2014). Evidence that BRAID-Learn can account for the evolution of eye movement patterns when repeatedly confronted to the same input strings is further evidence in support of its theoretical assumptions.…”
Section: The Mechanisms Of Orthographic Learningmentioning
confidence: 95%
“…Further evidence that VA span more specifically relates to reading subskills that reflect word-specific orthographic knowledge -like irregular word reading (Bosse & Valdois, 2009), reading speed (Lobier et al, 2013;van den Boer et al, 2015;van den Boer & de Jong, 2018) or the length effect in word reading (van den Boer et al, 2013) -supports a potential contribution of VA span to word-specific orthographic knowledge acquisition. More direct evidence comes from studies showing a link between VA span and spelling acquisition (Niolaki et al, 2020;van den Boer et al, 2015) and from studies showing that VA span modulates novel word orthographic learning (Bosse et al, 2015;Chaves et al, 2012;Ginestet et al, 2020;Marinelli et al, 2020). Without minimizing the role of phonological skills in orthographic acquisition, these findings suggest that visual factors independently contribute to the development of word-specific orthographic knowledge.…”
Section: Introductionmentioning
confidence: 99%